Peran Work-Life Balance dalam Memediasi Pengaruh Beban Kerja dan Stres Kerja terhadap Kinerja Karyawan - Bierhoff, Rainhart; Kusdiana, Shindi; Putri, Mauludia Mugianto; Azzhara, Calista Desi; Wahjoedi, Tri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to examine the role of work-life balance in mediating the relationship between workload, job stress, and employee performance using a Systematic Literature Review (SLR) approach. Referring to the PRISMA guidelines, this study systematically analyzed 20 scientific articles published in SINTA 4 and SINTA 5 accredited journals within the period of 2019–2025. The findings reveal a consistent pattern indicating that workload has a significant positive effect on job stress, while job stress negatively impacts employee performance. High workload, particularly in the form of task complexity and time pressure, contributes to increased psychological strain, which ultimately reduces productivity and work quality. Furthermore, this study highlights the strategic role of work-life balance as a mediating variable that is capable of reducing the adverse effects of job stress on employee performance. Employees who are able to maintain a balance between work demands and personal life tend to demonstrate better resilience, higher job satisfaction, and sustained performance levels despite high job demands. In the context of the digital era, where technological advancements intensify work demands and blur work-life boundaries, the implementation of work-life balance becomes increasingly critical. This study contributes theoretically by integrating organizational and psychological factors into a comprehensive conceptual framework. Practically, the findings provide insights for organizations to design flexible work policies that support employee well-being. Therefore, work-life balance is not only a mediating factor but also a key strategic element in enhancing sustainable employee performance.